Formation and fragmentation of 2-hydroxyethylhydrazinium nitrate (HEHN) cluster ions: a combined electrospray ionization mass spectrometry, molecular dynamics and reaction potential surface study - Zhou, Wenjing; Liu, Jianbo; Chambreau, Steven D; Vaghjiani, Ghanshyam L (Physical chemistry chemical physics : PCCP, 2023)
The 2-hydroxyethylhydrazinium nitrate ([HOCH 2 CH 2 NH 2 NH 2 ] + NO 3 − , HEHN) ionic liquid has the potential to power both electric and chemical thrusters and provide a wider range of specific impulse needs. To characterize its capabilities as an electrospray propellant, we report the formation of HEHN cluster ions in positive electrospray ionization (ESI) and their collision-induced dissociation. The experiment was carried out using ESI guided-ion beam mass spectrometry which mimics an electrospray thruster in terms of ion emission, injection into a vacuum and fragmentation in space. Measurements include compositions of primary ions in the electrospray plume and their individual dissociation product ion cross sections and threshold energies. The results were interpreted in light of theoretical modeling. To determine cluster structures that are comprised of [HE + H] + and NO 3 − constituents, classical mechanics simulations were used to create initial guesses; and for clusters that are formed by reactions between ionic constituents, quasi-classical direct dynamics trajectory simulations were used to mimic covalent bond formation and structures. All candidate structures were subject to density functional theory optimization, from which global minimum structures were identified and used for construction of reaction potential energy surface. The comparison between experimental values and calculated dissociation thermodynamics was used to verify the structures for the emitted species [(HEHN) n HE + H] + , [(HEHN) n (HE) 2 + H] + , [(HE) n +1 + H] + and [(HE) n C 2 H 4 OH] + ( n = 0-2), of which [(HE) 1-2 + H] + dominates. Due to the protic nature of HEHN, cluster fragmentation can be rationalized by proton transfer-mediated elimination of HNO 3 , HE and HE·HNO 3 , and the latter two become dominant in larger clusters. [(HE) 2 + H] + and [(HE) n C 2 H 4 OH] + contain H-bonded water and consequently are featured by water elimination in fragmentation. These findings help to evaluate ion formation and fragmentation efficiencies and their impacts on electrospray propulsion. The 2-hydroxyethylhydrazinium nitrate ([HOCH 2 CH 2 NH 2 NH 2 ] + NO 3 − , HEHN) ionic liquid has the potential to power both electric and chemical thrusters and provide a wider range of specific impulse needs.